Characteristics of spread-F at a temperate latitude station, Jamaica - Rastogi, R.G. (My University, 1989)
The characteristics of spread-F at a temperate latitude station vis-à-vis those at an equatorial station in the same longitude zone are described. Temperate latitude spread signature on the ionogram is shown to be due to a number of off-vertical reflections superimposed over the normal vertical p’-f trace. At temperate latitude, the background f region ionization seems to increase during spread-F conditions. Onset time of spread-F seems to increase with distance from the equator, being about 1930 hrs at the equator, about 2200 hrs at the anomaly crest region, and about 0000 hrs at temperate latitudes.
Keywords: Temperate latitude station; Jamaica; Spread-F